KETEPATAN PENGALOKASIAN, SELF ASSESSMENT SYSTEM, DAN TARIF PAJAK TERHADAP TAX EVASION BAGI WAJIB PAJAK ORANG PRIBADI - Putu Novia Hapsari Ardianti (UNHI Press, 2021)
Taxes have a very big influence in a country, without taxing state life will not work well. The role of tax revenue for a country is very dominant in supporting the running of government and development financing, however, the reality in the field is that the awareness of taxpayers in paying taxes is still low. This study aims to determine the effect of allocation accuracy, self-assessment system, and tax rates on tax evasion for individual taxpayers at the Kantor Pelayanan Pajak Pratama Tabanan. The study population was 200,947 individual taxpayers registered at the Kantor Pelayanan Pajak Pratama Tabanan. The sample in this study were 100 individual taxpayers who were determined based on the accidental sampling method. The analytical method used is multiple linear regression analysis which previously performed instrument tests, classical assumption tests (normality test, multicollinearity test and heteroscedasticity test) and model feasibility tests. The results showed that allocation accuracy and tax rates had positive effect on tax evasion, meanwhile self-assessment system had no effect on tax evasion. Suggestions based on this research are the Kantor Pelayanan Pajak Pratama Tabanan can use the results of this study as reference material to determine the policies needed to overcome tax evasion actions carried out by taxpayers. Future research is expected to add other independent variables to increase variation and find out other causes that can influence the tax evasion action.